EFEKTIFITAS PENAMBAHAN MANUAL LONGITUDINAL MUSCLE STRETCHING PADA CERVICAL STABILIZATION EXERCISE TERHADAP DISABILITAS & NYERI LEHER PADA KASUS MYALGIA CERVIKALIS (Lembaga Penerbitan Universitas Esa Unggul, 2017)
AbstractConsisting of Chapter VI, 76 pages, 13 tables, 11 pictures, 5 scheme, 19 attachments Objective: To determine differences of cervical stabilization exercise with Longitudinal Manual Muscle Stretching and cervical stabilization exercise on disability and neck pain in the cervical myalgia. Methods: The study randomized experimental with sample of 22 people, divided control group (n=11) and treatment group (n=11), where the disability and neck pain is measured and evaluated with the Neck Disability Index (NDI) and the Visual Analogue Scale (VAS), Sampling was conducted random sampling, while data analysis techniques to test the Shapiro Wilk normality test as a test, t-test related determine the effects of a sample in the same treatment group, and independent t-tests as a comparison test. Results: In the control group the value of NDI mean = 16.6 and SD = 8.5 to VAS mean = 2.5 SD = 1.3 with related t-test p value = 0.001. NDI value in the treatment group mean = 6.9 and the value SD = 2.8 to VAS mean = 0.9 and SD = 0.5 with a value related t-test p value = 0.000. On the test of independent t-test control group p value = 0.001 and p = 0.000 treatment group. Conclusion: Giving Longitudinal Manual Muscle Stretching and Cervical Stabilization Exercise is proven to reduce disability and neck pain due to cervicalmyalgia. Keywords : manual longitudinal muscle stretching, cervical stabilization exercise, myalgiaÂ AbstrakTujuan: Mengetahui perbedaan pemberian cervical stabilization exercise dengan Manual Longitudinal Muscle Stretching dan cervical stabilization exercise terhadap disabilitas dan nyeri leher pada kondisi myalgia cervicalis. Metode: Penelitian random eksperimental dengan jumlah sampel 22 orang, dibagi kelompok kontrol (n=11) dan kelompok perlakuan (n=11), dimana disabilitas dan nyeri leher diukur dan dievaluasi dengan Neck Disability Index(NDI) dan Visual Analogue Scale (VAS). Pengambilan sampel dilakukan teknik random sampling sedangkan teknik analisa data dilakukan uji saphiro wilk test sebagai uji normalitas data, uji t-test related mengetahui efek terhadap sampel pada kelompok perlakuan yang sama, dan uji t-tes independent sebagai uji pembanding. Hasil: Pada kelompok kontrol nilai NDI mean=16,6 dan SD=8,5 untuk VAS mean=2,5 SD=1,3 dengan uji t-test related didapatkan nilai p=0,001. Pada kelompok perlakuan nilai NDI mean=6,9 dan nilai SD=2,8 untuk VAS mean=0,9 dan SD=0,5 dengan nilai uji t-test related didapatkan nilai p=0,000. Pada uji t-tes independent kelompok kontrol didapatkan nilai p= 0,001 dan kelompok perlakuan p=0,000.Â Kesimpulan: Pemberian Manual Longitudinal Muscle Stretching dan Cervical Stabilization Exercise terbukti mengurangi disabilitas dan nyeri leher akibat myalgia cervicalis.Â Kata kunci : manual longitudinal muscle stretching, cervical stabilization exercise, myalgia